Causal relationships between service quality and user satisfaction. A systematic review of the literature - Vergara Schmalbach, Juan Carlos; Maza Avila , Francisco Javier (Universidad Francisco de Paula Santander, 2025)
The aim of this article is to identify the characteristics of research that incorporates causal relationships between perceptions of quality and the satisfaction of users receiving a service, in order to serve as a basis for the development of new empirical cases. For the development of this article, the systematic literature review technique was applied, following the PRISMA standard, defining the elements for the inclusion of documents and concluding in an individual synthesis, based on narrative or interpretation. The ScienceDirect and EBSCOHost databases were considered, covering content in the areas of Economic Sciences and/or Social Sciences. The search yielded 801 articles of which 68 were chosen for investigation and application of the selection criteria. In relation to the effect between perceptions and service user satisfaction, 95.59% of the studies provide a significant positive test between perceptions and satisfaction, coinciding with the disconfirmation approach and corroborating the theories that support it. Furthermore, the results suggest the need to comply with the requirements of the statistical methods used to solve causal models, starting with the definition of the representative sample size, the number of hypotheses proposed, the definition of the latent and observable variable, and the validation of the results.